Importance of Nutraceuticals in Health Management - V.S, Maddi; P.D, Aragade; V.G., Digge; M.N, Nitalikar (Pharmacognosy Reviews)
‘Nutraceutical’ is a term proposed to used a classify foods that ‘provide medical or health benefits’. Nutraceutical is any food or food ingredient considered to provide medical or health benefits including the prevention and treatment of disease. Dr Stephen DeFelice coined the term "Nutraceutical" from "Nutrition" and "Pharmaceutical" in 1989. The term nutraceutical is being commonly used in marketing but has no regulatory definition. Nutraceuticals and functional foods are assuming a middle ground between food and drugs due to growing body of evidence that supports their role in maintaining health and contributing to treatment of disease. “Traditional nutrient” refer to vitamins and minerals considered essential to the diet and / or to correct a classical nutritional deficiency disease, whereas “functional foods” may provide specific health benefits beyond basic nutrition when consumed a part of varied diet. Nutrient, herbals and dietary supplements are major constituents of nutraceuticals, which make them instrumental in maintaining health against various disease conditions and thus promote the quality of life. The focus of this article is to give a brief overview on Nutraceutical.
Keywords: Dietary supplement; Functional food; Medical food; Nutraceuticals